Trotzdem (Nevertheless) - Bagina, Elena (project baikal, 2021)
Adolf Loos’s works, regardless of all the circumstances, have been relevant for more than a century. Although Loos is called a functionalist, his architecture is beyond this definition. Loos can be considered as a master of Art Deco, if Art Deco is regarded as a worldview. Adolf Loos expressed his views on the nature of architecture in a number of articles and essays. The ideas expressed by Loos are not yet fully comprehended by architectural theorists. His Raumplan (Spatial Plan) is a unique planning method.